CHARACTERISTICS OF COVID-19 CASES IN PREGNANCY AT PROF DR I GUSTI NGOERAH GDE NGOERAH HOSPITAL IN 2021-2022 - Gde Ari Putra, Orion Reffa; Gede Fajar Manuaba, Ida Bagus; Sastra Winata, I Gde; Ngurah Harry Wijaya Surya, I Gede (E-Jurnal Medika Udayana; Vol 13 No 8 (2024): E-Jurnal Medika Udayana, 2024)
COVID-19 is a respiratory virus that can cause mild to severe respiratory illnesses and complications. Pregnant women and new mothers are at high risk for infection. This study aims to understand COVID-19 cases during pregnancy. The objective of this study was to determine the characteristics of COVID-19 cases during pregnancy at RSUP Prof Dr I Gusti Ngoerah Gde Ngoerah in 2021-2022. This descriptive observational cross-sectional study analyzed events occurring in the population without intervening in the study subjects. The results indicate that pregnant women with COVID-19 at RSUP Prof Dr I Gusti Ngoerah Gde Ngoerah in 2021-2022 were mostly aged between 20-30 years (64,3%), had one pregnancy (74,4%), and were in the third trimester (79,9%). The study found that (44,7%) of participants had a BMI indicating overweight, (100%) had no COVID-19 risk, and (48,2%) did not know their COVID-19 risk. Additionally, (97,5%) had not received a COVID-19 vaccination, (49,2%) experienced mild clinical symptoms, and (41,2%) were treated with remdesivir as an antiviral medication. The majority of participants had a high leukocyte count (54,3%) and normal platelet values (77,9%), but (68,3%) did not undergo lymphocyte count examination. (47,2%) of the majority did not undergo radiological imaging. For those who did, it was done for pneumonia in (30,7%) of cases.